Severe Acute Respiratory Syndrome Coronavirus 3a Protein Is a Viral Structural Protein - Ito, Naoto (American Society for Microbiology, 2005)
The present study showed the association of a severe acute respiratory syndrome coronavirus (SCoV) accessory protein, 3a, with plasma membrane and intracellular SCoV particles in infected cells. 3a protein appeared to undergo posttranslational modifications in infected cells and was incorporated into SCoV particles, establishing that 3a protein was a SCoV structural protein.